The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1101/2023.04.25.538210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Root branching in salt requires auxin-independent modulation of LBD16 function

Abstract: Salinity stress constrains lateral root (LR) growth and severely impacts plant growth. Auxin signaling is indispensable for the regulation of LR formation. Nevertheless, the molecular mechanism of how salinity affects root auxin signaling and whether salt would steer alternative pathway(s) to regulate LR development is unknown. Here we show that the auxin-regulated transcription factor LATERAL ORGAN BOUNDARY DOMAIN (LBD) 16, known as an essential player for LR development under control conditions, is regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Serotonin‐treated sunflower seedlings grown on NaCl demonstrated longer primary roots than untreated seedlings (Erland et al, 2016). Recently, salinity stress has been shown to inhibit LR growth and have a negative impact on Arabidopsis development (Xu et al, 2020; Zhang et al, 2023). It has been previously demonstrated that both serotonin and melatonin induce the expression of LATERAL ORGAN BOUNDARIES DOMAIN 16 ( LBD16 ) and XYLOGLUCAN ENDOTRANSGLYCOSYLASE RELATED 6 ( XTR6 ), which promote LR growth in Arabidopsis (Wan, Zhang, Wang, et al, 2018).…”
Section: Serotonin In Plant Fitness and Stress Tolerancementioning
confidence: 99%
See 2 more Smart Citations
“…Serotonin‐treated sunflower seedlings grown on NaCl demonstrated longer primary roots than untreated seedlings (Erland et al, 2016). Recently, salinity stress has been shown to inhibit LR growth and have a negative impact on Arabidopsis development (Xu et al, 2020; Zhang et al, 2023). It has been previously demonstrated that both serotonin and melatonin induce the expression of LATERAL ORGAN BOUNDARIES DOMAIN 16 ( LBD16 ) and XYLOGLUCAN ENDOTRANSGLYCOSYLASE RELATED 6 ( XTR6 ), which promote LR growth in Arabidopsis (Wan, Zhang, Wang, et al, 2018).…”
Section: Serotonin In Plant Fitness and Stress Tolerancementioning
confidence: 99%
“…It has been previously demonstrated that both serotonin and melatonin induce the expression of LATERAL ORGAN BOUNDARIES DOMAIN 16 ( LBD16 ) and XYLOGLUCAN ENDOTRANSGLYCOSYLASE RELATED 6 ( XTR6 ), which promote LR growth in Arabidopsis (Wan, Zhang, Wang, et al, 2018). Both LBD16 and XYLOGLUCAN ENDOTRANSGLUCOSYLASE 23 ( XTH23 )/ XTR6 play essential roles during salinity stress (Xu et al, 2020; Zhang et al, 2023). Furthermore, ZINC FINGER OF ARABIDOPSIS THALIANA 6 (ZAT6) has been shown to regulate LBD16 activity, which contributes to downstream cell wall remodelling and promotes LR development under salinity stress (Zhang et al, 2023).…”
Section: Serotonin In Plant Fitness and Stress Tolerancementioning
confidence: 99%
See 1 more Smart Citation